Β-Bi2O3 reduction by laser irradiation in a liquid environment. Issue 15 (3rd April 2018) - D'Angelo, D.; Filice, S.; Miritello, M.; Bongiorno, C.; Fazio, E.; Neri, F.; Compagnini, G.; Scalese, S.
Abstract : This study reports the structural and stoichiometric modifications of bismuth oxide nanoparticles in the β phase (β-Bi2 O3 ) by UV pulsed laser irradiation in water or ethanol solutions. Abstract : This study reports the structural and stoichiometric modifications of bismuth oxide nanoparticles in the β phase (β-Bi2 O3 ) by UV pulsed laser irradiation in water or ethanol solutions. Scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, UV-vis diffuse reflectance and high-resolution transmission electron microscopy were used to characterize the synthesized nanomaterials. The various analyses demonstrate that the laser irradiation of β-Bi2 O3 nanospheres is a green, fast and effective method to produce Bi2 O2 CO3 nanosheets or metallic Bi nanoparticles depending on the liquid environment used. Bi subcarbonate is obtained by laser irradiation in water, whereas metallic Bi is produced by laser irradiation in ethanol, and in particular the relative amount of metallic Bi is found to depend on the laser fluence. These typologies of materials find application in several fields, such as photocatalytic processes, light filters and environmental sensors.